Cerebral Amyloidoma Resulting from Central Nervous System Lymphoplasmacytic Lymphoma: A Case Report and Literature Review. (26th June 2018) - Jagannathan, Geetha; Uppal, Guldeep; Judy, Kevin; Curtis, Mark T.
Abstract : Cerebral amyloidomas are rare cerebral mass lesions often associated with significant morbidity. Cerebral amyloid accumulation can be the result of a number of disease states and it is crucial for proper patient care to identify the pathogenic process leading to amyloidoma formation. Low grade clonal B-cell processes are one cause of cerebral amyloidomas. We report a case of an 87-year-old woman who presented with a lymphoplasmacytic lymphoma associated cerebral amyloidoma complicated by cerebral hemorrhage, discuss the proper workup of this disease entity, and present a review of the literature on this topic.